Thermal transformation of synthetic euhedral and fibrillar crystals of boehmite into aluminas - De Souza Santos, Helena; Kiyohara, Pedro K.; De Souza Santos, Pérsio (Materials research bulletin, 1996)
Fibrillar pseudoboehmite and euhedral lath-like boehmite aqueous sols were prepared from the reaction of aluminium secondary butoxide and acetic acid in order to have a solid content of 70g/1 of AlOOH. The dried solids were fired from 200 °C to 1500 °C and examined by TEM, SEM, SAED, and XRD to compare formation of aluminas and their crystal morphological changes at the same temperatures. It was observed that the sequence of transformations of fibrillar pseudoboehmite is closer to that for euhedral boehmite than to the “gelatinous boehmite” described in the literature.